Scoping review of the potentials of fuzzy cognitive maps as a modeling approach for integrated environmental assessment and management. (January 2021) - Mourhir, Asmaa
Abstract: Fuzzy Cognitive Maps were missing in the latest guidance by Kelly et al. (2013), which reviewed five common integrated modeling approaches. Through a scoping review, the paper shows how Fuzzy Cognitive Maps satisfy key criteria for suitability in integrated environmental assessment, such as model purpose, types of data available to build a model, requirements in terms of spatial and temporal scales, stakeholder involvement, and treatment of uncertainty. The paper consequently updates the guiding framework that can be used by modelers to select the most appropriate modeling approach by including Fuzzy Cognitive Map techniques. We argue that the method can be the starting point of any integrated environmental assessment research to map out perspectives and potential system sensitivities. They constitute a great addition to the integrated assessment modeling toolbox as they can complement quantitative model approaches that are invariably constructed around a single perspective that relates to available data. Highlights: We review FCMs as an integrated environmental assessment modeling approach. FCMs can be the starting point of any environmental assessment research to map out perspectives and system sensitivities. FCMs can complement quantitative approaches that are invariably constructed around a single data-related perspective.